Peningkatan Komunikasi Belajar Matematika dengan strategi Partners In Learning Pada Siswa Kelas VII Semester Genap SMP N I Sambi Tahun 2014/2015 - hidayati, Nur, Prof. Dr. Sutama, M.Pd (2015)
Background of the research is caused by the lack of communication of mathematics in the learning process. The aim of this research is to describe the increasing communication of mathematics for VII C grade students of SMP N I Sambi with the application partners in learning strategies. Techniques of collecting data through observation, testing, field notes, and documentation. The implementation of class action carried out for two cycles consist of 4 meeting. The type of this research is descriptive qualitative through three stages: data reduction, data presentation, and data verification. The data validity uses triangulation of sources and methods. Results of the study are: (1) application of learning strategies in learning partners can improve communication math of VII C grade in SMP Negeri I Sambi, (2) there are increasing in communication of mathematics from baseline to the end of the second cycle, judging from 1) Students be able to ask the questions, answer, and concluded (verbal aspect) 53.13%, 2) Students be able to use mathematical symbols correctly and properly (aspect written) 43.75%, 3) Students be able to transform the problem into a settlement illustrations derived from tables, charts, and graphs (image asp ect) 50% 4) Students be able to complete and explain the mathematical solution (aspects solve problems) 56.25% , Based on the description above, it can conclude that the process of the mathematics learning with the application partner in learning strategies can improve mathematic communication students learning.